Longitudinal associations between metaphor understanding and peer relationships in middle childhood. Issue 4 (6th May 2021) - Del Sette, Paola; Ronchi, Luca; Bambini, Valentina; Lecce, Serena
Abstract: Metaphor understanding is a pragmatic inferential skill that serves a social function in adulthood. The present longitudinal study was designed to investigate the existence and the direction of the associations between metaphor understanding and peer relationships in children. One‐hundred twenty‐six typically developing 9‐year‐old children were tested at baseline and a year later for their ability to understand metaphors (via the physical and mental metaphors task) and their peer relationships (through peer acceptance and rejection). Results showed a longitudinal and bidirectional association between metaphor understanding and peer rejection, but not peer acceptance. Children who were more rejected were less able to understand metaphors 1 year later and children who struggled in understanding metaphors were more rejected 1 year later. Results are discussed in light of existing theoretical models. Overall, these findings show that the social nature of metaphor traces back to peer relationships in children.